The fate and the role of mitochondria in Fe-deficient roots of strategy I plants - Vigani, Gianpiero (Landes Bioscience, 2009)
In well aerated soils, iron exists, mainly as scarcely soluble oxides and oxi-hydroxides and, therefore, not freely available to plants uptake, notwithstanding its abundance. Multifaceted strategies involving reductase activities, proton processes, specialized storage proteins, and other, act in concert to mobilize iron from the environment, to take it up and to distribute it inside the plant. Because of its fundamental role in plant productivity several questions concerning homeostasis of iron in plants are currently a matter of intense debate. We discuss some recent studies on Strategy I responses in dicotyledonous plants focusing on metabolic change induced by iron deficiency, mainly concerning the involvement of mitochondria.